2020
DOI: 10.1016/j.xcrm.2020.100140
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Links Myeloid Activation and Disease Progression in Systemic Sclerosis

Abstract: Summary Progressive lung fibrosis is a major cause of mortality in systemic sclerosis (SSc) patients, but the underlying mechanisms remain unclear. We demonstrate that immune complexes (ICs) activate human monocytes to promote lung fibroblast migration partly via osteopontin (OPN) secretion, which is amplified by autocrine monocyte colony stimulating factor (MCSF) and interleukin-6 (IL-6) activity. Bulk and single-cell RNA sequencing demonstrate that elevated OPN expression in SSc lung tissue is enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…Intriguingly, increased levels of SPP1 were associated with more favorable outcomes in IPF, in contrast to the rest of the ILDs. Circulating OPN was recently associated with immune complexes-driven profibrotic macrophage activity in SSc-ILD ( 55 ) and it could be speculated that OPN plays a more significant role in autoimmune-driven fibrosis as compared to IPF. Furthermore, recent studies with models of tissue repair and scar formation following heart injury showed that osteopontin expressing recruited macrophage populations play both a pro-fibrotic and pro-resolving role ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, increased levels of SPP1 were associated with more favorable outcomes in IPF, in contrast to the rest of the ILDs. Circulating OPN was recently associated with immune complexes-driven profibrotic macrophage activity in SSc-ILD ( 55 ) and it could be speculated that OPN plays a more significant role in autoimmune-driven fibrosis as compared to IPF. Furthermore, recent studies with models of tissue repair and scar formation following heart injury showed that osteopontin expressing recruited macrophage populations play both a pro-fibrotic and pro-resolving role ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…58 A recent paper with IPF shows that Spp1 is primarily expressed in myeloid cells in interstitial pulmonary fibrosis and IL-6 stimulates OPN expression in macrophages, which sensitizes and mobilizes fibroblasts toward other fibrogenic growth factors. 59 Accordingly, it is likely that one major outcome of SPP1 deficiency is altered immune cell type distribution and activation, which possibility will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression of bulk scleroderma specimens of skin often does not reveal up-regulation of AREG in the diseased biopsies although a recent report showed up-regulation in scleroderma patients [ 41 ]. However, activated immune cells from scleroderma show a high level of Areg expression [ 42 ], indicating that expression of AREG is associated with specific cell types in the disease process, rather than the overall gene expression. Indeed, single cell analyses indicate that AREG is highly expressed in myofibroblasts, not other types of fibroblasts in scleroderma patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%